1996
DOI: 10.1161/01.cir.94.11.2793
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Placebo-Controlled Study of the Effects of Carvedilol in Patients With Moderate to Severe Heart Failure

Abstract: These findings indicate that, in addition to its favorable effects on survival, carvedilol produces important clinical benefits in patients with moderate to severe heart failure treated with digoxin, diuretics, and an ACE inhibitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
250
0
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 558 publications
(272 citation statements)
references
References 40 publications
11
250
0
11
Order By: Relevance
“…However, exercise tolerance has not been consistently improved with carvedilol in clinical trials in heart failure,28, 29, 30 and treatments that have improved symptoms and exercise tolerance have not produced striking effects on cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…However, exercise tolerance has not been consistently improved with carvedilol in clinical trials in heart failure,28, 29, 30 and treatments that have improved symptoms and exercise tolerance have not produced striking effects on cachexia.…”
Section: Discussionmentioning
confidence: 99%
“…29 Left ventricular hypertrophy can be reduced by the peripheral and coronary vasodilating effect of ␣-blockade. 11,28,30 The beneficial effect of adrenergic suppression on mortality and hospitalization rates in adults has been demonstrated in several large-scale studies with metoprolol 13,14 and bisoprolol. 15,16 In adults with CHF who were treated with digoxin, diuretics and ACE inhibitors, the addition of carvedilol significantly reduced mortality and hospitalization rates.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies 8 -10 in adult patients have suggested that sympathetic activation plays an important role in the genesis and progression of heart failure. This, combined with the results of several clinical trials, [11][12][13][14][15][16] has led to the addition of ␤-sympathetic antagonists to the armamentarium of pharmacologic treatments for heart failure in adults. Carvedilol is a third generation non-selective ␤-antagonist with ␣ 1 -adrenergic blocking and anti-oxidant activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because HF hospitalization can be defined in various ways, and in order to ensure sufficient data for a meaningful analysis, data for surrogate measures of HF hospitalization were used in a number of studies 4, 5, 6, 7, 8, 9. The surrogate measures consisted of ‘ worsening heart failure requiring intravenous diuretic therapy or discontinuation of the study ’, ‘ intravenous furosemide for the control of acute exacerbations or symptoms ’, ‘ heart failure episode/decompensation ’, ‘ hospitalization for cardiovascular causes/reasons ’, ‘ cardiovascular hospitalization ’, and ‘ severe/resistant heart failure ’.…”
Section: Methodsmentioning
confidence: 99%